Effects of filler type and aging on self-sensing capacity of cement paste using eddy current-based nondestructive detection. (September 2021) - Meng, Xiao; Feng, Ju; Pai, Ning; Zequan, He; Kaiyuan, Li; Cheng, Zhou; Yazhen, Zhang
Highlights: A non-destructive method based on eddy current for self-sensing concrete is proposed. The self-sensing ability of plain mortar is studied using eddy current testing method. Steel fiber is proved to improve self-sensing ability of concrete. The effect of curing time on concrete with or without fillers is studied. Abstract: Eddy current-based nondestructive detection was first used for testing self-sensing cement paste in this study. The effects of three functional fillers and aging on self-sensing cement paste were observed. First, the plain mortar exhibited self-sensing ability at the earliest curing time, but its gage factor significantly decrease with ages. Second, among the three functional fillers that were studied - carbon fiber (CF), steel fiber (SF), and carbon black (CB) - the SF exhibited the highest gage factor. Third, the effect of ages on eddy current sensitivity is not obvious. The gage factor SF-reinforced specimens is high in different ages, while the gage of CF- and CB-reinforced specimens change little with ages. This study shows that eddy current-based nondestructive detection is feasible to detect stress and damage-induced variation of cement paste, and SF is the best filler to improve the self-sensing ability of cement paste.